Triassic and Jurassic beds in Krim Mountain area (Slovenia) - Miloš Miler; Jernej Pavšič (Geologija, 2008)
The Krim Mountain and its surroundings are characterized by Upper Triassic to Middle Jurassic rocks, which were deposited on the northern margin of the Dinaric Carbonate Platform. Upper Triassic beds are represented by Main dolomite that exhibits supra- to subtidal Lofer facies. The uppermost Triassic is characterized by approximately 40 m thick horizon of dolomitic breccia. Upper Triassic beds pass gradually into Lower Liassic dolomitic breccia, coarse-grained dolomite and micritic limestone. Presence of dolomitic breccias and absence of supra-intertidal sedimentary structures indicate sea-level rise. Middle Liassic beds consist of oolitic-oncolitic and lithiotid limestones deposited in alternating restricted lagoonal and open shallow-water environment. Upper Liassic beds are characterized by oolitic-oncolitic limestones, bituminous dolomitized limestones and dolomitic breccia deposited in high-energy shallow-water environment. Middle Jurassic beds consist of oolitic, oolitic-oncolitic and micritic limestones, formed predominantly in high-energy subtidal environment.